Fintech Lending, Consumer Behavior, and Financial Management Behavior: Moderating Effect of Financial Literacy - Verliani Dasmaran; Muhamad Agung Dharmajaya (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The rapid growth of fintech lending services among university students has increased financial access but also raised concerns about irresponsible borrowing and poor financial management. The study aimed to examine the effects of fintech lending and consumer behavior on individual financial management behavior, with financial literacy serving as a moderating variable. A quantitative research design with a cross-sectional survey approach was employed, involving 400 accounting students from nine universities in Banten Province, Indonesia. Data were collected through online questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings revealed that fintech lending had a positive and significant effect on individual financial management behavior, while consumer behavior showed no significant effect. In addition, financial literacy significantly weakened the relationship between fintech lending and individual financial management behavior, indicating that financially literate individuals tend to use digital lending services more cautiously and rationally. However, financial literacy did not significantly moderate the relationship between consumer behavior and financial management behavior. These findings highlight the importance of strengthening financial literacy programs to encourage responsible financial decision-making among university students.